The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1055/s-2007-1021042
|View full text |Cite
|
Sign up to set email alerts
|

Choice Reaction Time During Graded Exercise in Relation to Blood Lactate and Plasma Catecholamine Thresholds

Abstract: Twenty-two male soccer players (mean age 21.3 yrs) performed an incremental, multistage bicycle ergometer exercise test with work load increasing by 50 W, until volitional exhaustion. The exercise stages lasted 3 min and were separated by 1 min resting periods. Before exercise and during each load an audio-visual five-choice reaction task was administered to assess subjects' psychomotor performance. During resting intervals venous blood samples were taken for lactate (LA), adrenaline (A) and noradrenaline (NA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
211
3
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(235 citation statements)
references
References 15 publications
18
211
3
3
Order By: Relevance
“…These authors claimed that mental improvement during exercise may be the consequence of central noradrenergic activation. Moreover, Chmura et al (1994Chmura et al ( , 1998 have shown that there is a significant correlation between the concentration of plasma catecholamines and reaction time during exercise in man. Chmura et al (1994Chmura et al ( , 1998 claimed that increased concentrations of catecholamines in the central nervous system during exercise should induce an improvement in performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors claimed that mental improvement during exercise may be the consequence of central noradrenergic activation. Moreover, Chmura et al (1994Chmura et al ( , 1998 have shown that there is a significant correlation between the concentration of plasma catecholamines and reaction time during exercise in man. Chmura et al (1994Chmura et al ( , 1998 claimed that increased concentrations of catecholamines in the central nervous system during exercise should induce an improvement in performance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Chmura et al (1994Chmura et al ( , 1998 have shown that there is a significant correlation between the concentration of plasma catecholamines and reaction time during exercise in man. Chmura et al (1994Chmura et al ( , 1998 claimed that increased concentrations of catecholamines in the central nervous system during exercise should induce an improvement in performance. Based on brain catecholamines, Pagliari and Peyrin (1995a, b) found a positive correlation between central noradrenergic activation during exercise and peripheral adrenaline secretion in rats.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with Chmura et al. 10 showing that cortical neuroelectric activity increases with increasing intensity of physical exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate workload exercise has the potential to improve cognitive performance [7][8][9][10][11][12][13], by increasing central nervous activation and sensory sensitivity [17]. In order to assess the effect of both associative and dissociative sessions on central nervous activation we used the critical licker fusion (CFF) frequency test.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate physical exercise has the potential to improve cognitive performance [6][7][8][9][10][11][12][13]. In addition, acute physical exercise has showed small positive effects on cognitive performance [14].…”
Section: Introductionmentioning
confidence: 99%